A20 controls expression of beta cell regulatory genes and transcription factors. (August 2021) - Ratajczak, Wiktoria; Atkinson, Sarah D; Kelly, Catriona
Abstract : TNFAIP3 encodes a zinc finger protein called A20, which has potent anti-inflammatory and anti-apoptotic properties. A20 promotes beta cell survival and protects against islet graft rejection in experimental models. The current study sought to investigate the mechanisms underlying the protective role of A20 in the pancreatic beta cell. Two islet cell types were used for experiments: the insulin-secreting BRIN-BD11 cell line and human islet cells. A20 was silenced using siRNA against TNFAIP3 and knockdown confirmed by qPCR and immunostaining of cells. Cell viability, cytotoxicity and apoptosis was assessed using the ApotoxGlo assay. Glucose-stimulated insulin secretion and production of inflammatory cytokines (TNFa, IL1b and IFNg) were measured by ELISA. Expression of beta cell regulatory genes (Abcc8, Kcnj11, Kcnq1, Gck, Scl2a2) and transcription factors (Hnf1a, Pdx1, Nkx6.1, Ngn3) was determined by qPCR. A20 deficiency increased apoptosis, impaired glucose-induced insulin secretion, and reduced expression of beta cell regulatory genes and transcription factors. Addition of recombinant A20 normalized gene expression profiles. TNFa, IL1b and IFNg were elevated in A20 deficient cells and found to independently elicit changes in gene expression. Analysis of PCR array data suggests that A20 action in the beta cell is largely, although not exclusively, driven by the P65 subunit of NF-kB. The current report demonstrates a role for A20 in controlling beta cell integrity and survival, which likely results from regulation of inflammatory signaling. Of particular note is the impact that A20 deficiency has on the expression of transcription factors regulating the maturation and normal function of beta cells.